2021
DOI: 10.1159/000514995
|View full text |Cite
|
Sign up to set email alerts
|

Facial Skin Biophysical Profile of Women in Malaysia: Significance of Facial Skincare Product Use

Abstract: <b><i>Introduction:</i></b> At present, there is a lack of baseline data on the facial skin biophysical profile of women in Malaysia. The implications related to the daily habits and facial skincare product use on the skin biophysical condition are, thus, unknown. In this study, we aim to evaluate facial skin biophysical parameters of Malaysian women and examine the influence of demographic characteristics, daily habits, and facial skincare product use on these parameters. <b><… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…Recently, Goh et al 74 . reported that Malaysian women have higher elasticity on the facial cheek than the females in the nearby countries as reported by Lee et al 73 .…”
Section: Biophysical Properties Of Asian Skinmentioning
confidence: 84%
See 4 more Smart Citations
“…Recently, Goh et al 74 . reported that Malaysian women have higher elasticity on the facial cheek than the females in the nearby countries as reported by Lee et al 73 .…”
Section: Biophysical Properties Of Asian Skinmentioning
confidence: 84%
“…reported a drop in elasticity and an increase in wrinkles with aging which are similar for all Asian subjects. Likewise, Goh et al 74 . also observed a reduced facial cheek elasticity and collagen with an increase in melanin content among elder Malaysian women.…”
Section: Biophysical Properties Of Asian Skinmentioning
confidence: 85%
See 3 more Smart Citations